Gothic literature - Smith, Andrew, 1964- (Edinburgh critical guides to literature., 2013)
New edition of bestselling introductory text outlining the history and ways of reading Gothic literature. This revised edition includes: A new chapter on Contemporary Gothic which explores the Gothic of the early twenty first century and looks at new critical developments, an updated Bibliography of critical sources and a revised Chronology. The book opens with a Chronology and an Introduction to the principal texts and key critical terms, followed by five chapters: The Gothic Heyday 1760-1820; Gothic 1820-1865; Gothic Proximities 1865-1900; Twentieth Century; and Contemporary Gothic. The discussion examines how the Gothic has developed in different national contexts and in different forms, including novels, novellas, poems, films, radio and television. Each chapter concludes with a close reading of a specific text - Frankenstein, Jane Eyre, Dracula, The Silence of the Lambs and The Historian - to illustrate ways in which contextual discussion informs critical analysis. The book ends with a Conclusion outlining possible future developments within scholarship on the Gothic. --